Fluid and Electrolyte Management in the Neonate: Sodium and Chloride - Moss, Colleen Reilly (Neonatal network, 2022)
Maintenance of electrolyte balance in the neonate is a challenge in the context of illness or prematurity. Neonatal providers' approach to fluid management changes and adapts based on the newborn's age, maintenance needs, deficits, and ongoing losses. Understanding the total body water content of the fetus and newborn is foundational to management of electrolyte disturbances. This article reviews common imbalances of sodium and chloride, identifies causes of imbalances, and discusses current evidence-based treatment options.